SINKRONISASI PENGATURAN KEDUDUKAN BOEDEL PAILIT SEBAGAI BARANG BUKTI DALAM SISTEM HUKUM KEPAILITAN DAN HUKUM PIDANA DI INDONESIA - Sitompul, Laurendcius Pangihutan (Universitas Labuhanbatu, 2025)
This study aims to analyze the synchronization of regulations concerning the legal status of a bankrupt debtor’s assets (boedel pailit) as evidence within Indonesia’s bankruptcy and criminal law systems. The issue arises from the overlap of authority between the curator, who is responsible for managing the bankrupt estate for the benefit of creditors, and the investigator, who holds the authority to seize evidence in criminal proceedings. This research employs a normative juridical method using statutory and conceptual approaches, by examining relevant laws and regulations such as the Bankruptcy Law and the Indonesian Criminal Procedure Code (KUHAP), as well as scholarly opinions. The findings reveal that there is insufficient synchronization between bankruptcy law and criminal law, potentially resulting in legal uncertainty and conflicts of authority in practice. Therefore, clearer and more integrated regulation is required to ensure a balance between the objectives of criminal law enforcement and the protection of creditors’ rights in bankruptcy proceedings.Keywords: Legal Synchronization; Bankrupt Estate; Evidence; Bankruptcy Law; Criminal Law